Unlocking Nature's Bounty: Exploring the Ecotourism Potential of Batu Jongjong in Bahorok District, Langkat District - Yanti, Dewi; Khadry, Muhammad; Sianipar, Christina Indriany (Jurnal Ilmiah Global Education, 2024)
The research on community-based ecotourism in Batu Jongjong Village, Langkat Regency, explores its potential, inspired by rich natural and cultural resources. Located in Gunung Leuser National Park, the village benefits from biodiversity. Aimed at enhancing local welfare through sustainable ecotourism, the study stresses community participation and collaboration among stakeholders. Sustainability concepts, including resource protection, are crucial for long-term contributions. The unique aspect lies in empowering locals and ensuring shared responsibility for resource preservation. Batu Jong Jong Village, despite its potential, requires improvements in accessibility, management, and services for competitiveness. Challenges necessitate collaborative efforts, while opportunities lie in sustainable development, emphasizing economic, social, and environmental benefits. Designated as a tourist village, Batu Jong Jong holds promise for eco-tourism, utilizing its natural resources. Despite obstacles, the village's fertile soil and community involvement present a foundation for sustainable tourism, contributing to its long-term success.